1964
DOI: 10.1021/bi00899a012
|View full text |Cite
|
Sign up to set email alerts
|

Circular Dichroism of Poly-L-tyrosine*

Abstract: Circular-dichroism measurements of solutions of poly-L-tyrosine in the helical conformation at pH 11.2 reveal three ellipticity bands at 270, 248, and 224 µ. The band at 224 µ, which is the ro-TT* peptide transition characteristic of helical polypeptides, is negative in sign and indicates that the poly-L-tyrosine helix is right-handed. From the measured dichroism bands and an estimate of the contribution of an additional peptide transition at 190 µ, an optical rotatory dispersion curve was computed and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

1965
1965
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(52 citation statements)
references
References 10 publications
4
47
0
1
Order By: Relevance
“…Such 0.r.d. and circular dichroisin studies of poly-L-tyrosine (18,19) in aqueous media revealed this negative Cotton effect and circular dichroic band, further confirming the right-handed sense of the helix of this polymer. The optical rotation of solutions of poly-L-tryptophan in DXIF could only be determined do\\;n to 300 inp because of the absorbance of the solvent, and no other transpareilt helix-promoting solvent for this polymer could be found.…”
Section: E X C Obtained From a Drude Plotmentioning
confidence: 61%
See 1 more Smart Citation
“…Such 0.r.d. and circular dichroisin studies of poly-L-tyrosine (18,19) in aqueous media revealed this negative Cotton effect and circular dichroic band, further confirming the right-handed sense of the helix of this polymer. The optical rotation of solutions of poly-L-tryptophan in DXIF could only be determined do\\;n to 300 inp because of the absorbance of the solvent, and no other transpareilt helix-promoting solvent for this polymer could be found.…”
Section: E X C Obtained From a Drude Plotmentioning
confidence: 61%
“…However, poly-L-tyrosine was sho\vn by 0.r.d. studies (17,18) and circular dichroism (19) studies to be a right-handed helix. Consequently, the positive bo value must be due to the contribution of the chroinophoric side chains on the P-carbon which contributes to the rotation in the visible region of the spectrum.…”
mentioning
confidence: 99%
“…The optical rotatory properties of poly-L-tyrosine or tyrosine-rich peptide (TRP) have been reported to be very different from those of common peptides [47][48][49][50][51][52][53][54] . A TRP with a right-handed a-helical conformation has four p-p* side-chain transitions (analogous to the A 1g , B 1u , B 2u and E 1u states of benzene) at about 200, 230 and 280 nm in neutral aqueous solution [51][52][53] .…”
Section: Resultsmentioning
confidence: 99%
“…FAD [37], iron [38], copper [19] or molybdenum [38] complexes. I n the spectral region of 230 to 310-nm Cotton effects originating from cofactors are superimposed by those caused by side chain residues of amino acids like L-cystine [39], L-phenylalanine [39], L-tyrosine [40] or L-tryptophan [41,42]. The Cotton effects of the peptide bonds are located in the spectral region of 185-230 nm [43 to 461.…”
Section: Interpretation Of Circular-dichroism Datamentioning
confidence: 99%